Understanding spatial heterogeneity of hidden hunger in Senegal - Marivoet, Wim; Ulimwengu, John M.; Sall, Leysa Maty; Fall, Cheickh Sadibou (Informa UK Limited, 2025)
Using household consumption data collected in 2017/18, this paper analyzes patterns of urban and rural food consumption in Senegal. We adopt two methodological approaches: an in-depth (spatial) profiling of current diets and corresponding nutrient intakes and an application of the Quadratic Almost Ideal Demand System (QUAIDS). Our findings indicate that Senegal is a typical case of micronutrient deficiency, especially regarding calcium, iron, and vitamin B12. Due to their higher income status and better food access, urban dwellers on average have a more diversified diet with higher nutrient intakes compared to their rural counterparts, especially regarding calcium, vitamin B12, and vitamin A. While the country’s food system in general is unable to assure a nutritious diet for all, the most remote rural departments in Senegal, such as Saraya and Podor, display the highest nutrient deficiencies and therefore should be targeted with priority. Apart from geographical targeting and given their higher responsiveness to price and income changes, policies based on food pricing and income transfers should be implemented to ensure a minimal nutrient intake among the most food-insecure households. These policies could be further complemented with behavioral change campaigns to promote an alternative set of nutrient-rich and cost-effective food items.